PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN: KAJIAN LITERATUR TENTANG PENDEKATAN, TANTANGAN DAN SOLUSI - Saepul Anwar, Usep; Karim, Abdul; Suherman, Suherman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of educational human resources (HR) plays an important role in creating a quality and competitive education system. This research aims to examine various challenges and solutions in the development of educational human resources, focusing on the role of educators, including teachers, lecturers and principals, in creating an effective and innovative education system. The research method used is a literature study, where data is obtained from analyzing relevant scientific papers to gain a deeper understanding of related issues. The results show that educators' qualifications and competencies have a significant impact on education quality. Educators' professionalism and work motivation contribute to improved performance and innovation in education. In addition, the development of education human resources is faced with challenges such as the lack of qualified educators, the dynamics of social and technological change, and the unbalanced distribution of education human resources. Based on these results, recommendations include increased investment in educator training and professional development, curriculum adaptation that is responsive to current and future needs, and evidence-based implementation strategies to overcome barriers to HRD. As such, this research provides important insights into how countries can improve the quality and competitiveness of education systems through effective HRH development.